Quand la compétence traductologique dépasse la compétence rédactionnelle - Tomaszkiewicz, Teresa (Studia Romanica Posnaniensia, 2003)
This article discusses a characteristic style of John Paul II' homilies, delivered during his first pilgrimage to Poland in 1979. The author touches the question of the censorship who had an influence on the way of translating these texts and ponders the limits of liberty and faithfulness of a translator who prepares his translations in a definite social and political context.